ANALISIS TERHADAP UPAYA PENCITRAAN PERGURUAN TINGGI - Hartini, Tin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
There is a competition among universities in Indonesia that encourage them to build images or a public perception toward their institutions or their products. The positive images of an institution are beneficial for the institution itself. As an example, an organization or educational institution with positive images will have more loyal employees or obtain more students. Islamic University of 45 Bekasi (Unisma) builds its image as a university with Islamic characters in which its students, employees, and lecturers are encouraged to hold Islamic values in their academic or non-academic activities. The present study shows that these Islamic values can be considered as the strength of UNISMA in its academic, research, and community service as it gradually builds its standard of a university with Islamic characteristics. Besides that, this research shows that the implementation of public relation programs in their efforts to build an image of university can be considered as strategic policies done by public relation practitioners by combining various social needs and a promotional approach toward the strength of university. As an impact, practitioners are encouraged to understand the demands and aspirations of public as the existence of a university depends on public